COVID-19 restrictions on religious worship:how to ensure effectiveness while respecting religious autonomy? (Stato, Chiese e pluralismo confessionale, 2022)
TABLE OF CONTENTS: 1. Introduction - 2. The existing model of Coronavirus restrictions and its impact on freedom of religion - 3. Towards a new model of restriction - 4. Advantages of the new model of restrictions - 5. Safeguarding compliance with restrictions - 6. Conclusions.ABSTRACT: The topic of the article is to evaluate legal measures aimed to stop the spread of the coronavirus that limited religious rights. The restrictions are assessed from the perspective of its effectiveness in preventing infection as well as its proportionality. The argument is that proportionality of the restrictions depends on their effectiveness, which in turn should be evaluated in the light of current pandemic situation, which includes vaccination level and scientific knowledge on coronavirus transmission. Consequently, two kinds of restrictions are distinguished: premises-oriented and activities-oriented. The former focuses mainly on the capacity of the church premises and not so much on the activity of the gathered, whereas the latter pays attention to the activates of the worshippers, including religious practices. Given the epidemiological effectiveness and the balance between protecting public health and religious freedom, activities-oriented restrictions are identified as a proper model of restrictions.